Peningkatan prestasi belajar PAI melalui model cooperative learning pada materi beriman kepada Allah siswa kelas VII E SMP Negeri 5 Sukoharjo tahun ajaran 2022/2023 - Astriana Yustika; Nur Hidayah; Sugiyat (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This study was conducted to determine the improvement of student learning achievement in PAI learning in class VII E of SMP Negeri 5 Sukoharjo in 2023 by using the Cooperative Learning learning model. This study used class action research through the stages of planning, implementation, observation, evaluation and reflection. Data collection is done by test method. Data analysis used comparative descriptive and continued with reflection. The results showed that the application of the Cooperative Learning model can improve PAI learning achievement on the material of faith in Allah. Shown by the increasing value and class average in each cycle action. From the pre-cycle the average value of the class was 63.9375 with a learning completeness of 46.87%, cycle 1 the average value increased to 73.8175 with a learning completeness of 59.38%, cycle 2 the average value of the class was 84.00 with a classical learning completeness of 90.63%. With this, the research shows that the use of the Cooperative Learning model can increase the average score of students on the material of Believing in Allah class VII E SMP N 5 Sukoharjo so that there are no more students who are below the KKM.